Characterization Of The Piezoelectric Patch Sensor And Actuator - Murad, Ahmad Firdaus (Universiti Sains Malaysia, 2017)
The study presents the characterization of the piezoelectric patch as a sensor and actuator and its application for the active vibration control (AVC) system. Piezoelectric patch is a versatile component due to its dual-functionality which can be used as sensor and actuator and it corresponds to the mechanical and electrical energy conversion. This study consider the beam structure and the EMA result shows that, there are four natural frequencies of the beam which occurred at 30.4 Hz, 227.9 Hz, 709.9 Hz and 923.9 Hz. For the characterization of the piezoelectric patch actuator, the highest beam acceleration of 315.08 m/s2 is achieved at operating frequency of 200 Hz with 500 V due to the effect of second natural frequency (227.9 Hz) of the beam. The saturation effect starts to occur at the operating frequency of 300 Hz with 300 V of input voltage. The piezoelectric patch continues to saturate within operating frequencies of 300 Hz to 500 Hz with the input voltages of 300 V to 500 V. The result also shows that, the non-linearity effects such as hysteresis, creep and vibrational effects are getting worse, as the operating frequencies and voltages increase above 200 Hz with 200 V for the actuator. In term of piezoelectric patch sensor, the highest output voltage induced by the patch is 4.43 V at operating frequency of 200 Hz with 500 V which is caused by the resonance frequency of the beam. However, the piezoelectric patch does not experience any saturation effect within 100 Hz to 500 Hz with 100 V to 500 V and this corresponds to the FRF of the aluminium beam. The piezoelectric patch sensor is effective at frequency of 100 Hz and 200 Hz due to less non-linearity effects (hysteresis, creep and vibrational effects). As the frequency gets higher, the effects becomes significant and resulting large hysteresis formation. This study also includes the application of the piezoelectric patch actuator for AVC system. The result shows the patch is capable to reduce the vibration up to 42 % at frequency of 100 Hz with 100 V. However, the percentage of acceleration reduction decreases as the operating voltage is getting higher.